How should we define health?. (26th July 2011) - Huber, Machteld; Knottnerus, J André; Green, Lawrence; Horst, Henriëtte van der; Jadad, Alejandro R; Kromhout, Daan; Leonard, Brian; Lorig, Kate; Loureiro, Maria Isabel; Meer, Jos W M van der; Schnabel, Paul; Smith, Richard; et al.
Abstract : The WHO definition of health as complete wellbeing is no longer fit for purpose given the rise of chronic disease. Machteld Huber and colleagues propose changing the emphasis towards the ability to adapt and self manage in the face of social, physical, and emotional challenges